PENGARUH INTERVAL WAKTU SERTA PEMBERIAN KOMPOS KULIT BUAH PISANG TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG (Zea mays Saccharata L.): PENGARUH INTERVAL WAKTU SERTA PEMBERIAN KOMPOS KULIT BUAH PISANG TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG (Zea mays Saccharata L.) - Wibowo, Fadli; Irwan Agusnu Putra; Tanjung, Razali (Agroprimatech, 2023)
The aim of the research was to determine the effect of time intervals and the provision of banana peel compost on the growth and production of corn plants. This research was carried out at the People's Garden, Kel. Jati Utomo District. North Binjai. Binjai City, North Sumatra, in October 2022 - January 2023. The research used a factorial randomized block design (RAK) with 2 treatment factors, the first factor was time interval, namely W0 = 10 days before planting, W1 = 20 days before planting, W2 = 30 Days Before Planting. Second Factor Banana Peel Compost Fertilizer (P); P0 = No Application, P1 = 60 grams/plant ~ 960 grams/plot, P2 = 120 grams/plant ~ 1,920 grams/plot, P3 = 180 grams/plant ~ 2,880 grams/plot. The parameters observed were plant height, number of leaves, leaf area, wet weight of cobs with husks, wet weight of cobs without husks and dissolved solid sugar content. The research results showed that time interval treatment had a significant effect on all parameters, where the W1 treatment (20 days before planting) was the best. The banana peel compost treatment had a significant effect only on the parameters of plant height, number of leaves and leaf area and the P1 treatment (60 grams/plant) was the best, but had no significant effect on the parameters of cob weight with husks, cob weight without husks and soluble solid sugar content.